Strategi Pemasaran Skincare Herbal Sr12 Dengan Pendekatan Marketing Mix Untuk Meningkatkan Jumlah Pelanggan Pt. Xyz - Irma Dani Br Sinulingga; Mega Cattleya PA Islami (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
XYZ of the many types of promotions that have been carried out so far, it is not yet known to what extent their effectiveness is in increasing the number of customers at PT XYZ. Every business must have a marketing strategy that must be implemented in carrying out its business activities. This research aims to determine marketing strategies using a marketing mix approach consisting of product strategy, promotion strategy, price strategy and sales location strategy. The method used in this research is descriptive qualitative, namely a method that tries to explain and analyze phenomena, events, social dynamics, behavior and opinions of a person or group towards something. Based on the results of the marketing mix strategy analysis, it was obtained: product strategy, selling beauty products, namely herbal skincare such as: herbal manjakani, forest honey, v-co oil, date palm juice, etawa goat's milk, and lemon juice. Pricing strategy, setting the price of the product by looking at the quality level and net product, the product is set at a price of IDR 34,500.00 IDR 131,500.00. Place strategy, selling products via e-commerce via the Shopee application Promotion strategy, promoting products via social media (Tiktok, Instagram, YouTube and the company's official website).